2020
DOI: 10.1111/eci.13320
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery decreases oxidative stress and protein glycosylation in patients with morbid obesity

Abstract: Background: There is growing evidence that oxidative stress (OS) is a critical factor linking obesity with its associated comorbidities, such as cardiovascular diseases. Aim: To evaluate the degree of OS in people with morbid obesity and its relationship with glycoproteins, determined using 1H-NMR spectroscopy, before and after bariatric surgery (BS). Methods: In this observational cohort study, plasma from 24 patients with BMI ≥ 40 kg/m 2 (age: 21-65 years) was used to measure metabolites implicated in OS. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Furthermore, bariatric surgery may be a useful therapy for people who have cardiovascular risk factors [37]. Also, bariatric surgery decreases oxidative stress parameters and glycoproteins and increases antioxidant enzymes paraoxonase-1 and catalase as well, which supports the idea that this procedure decreases oxidation of lipoproteins thus having antiatherogenic effects [34,35].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, bariatric surgery may be a useful therapy for people who have cardiovascular risk factors [37]. Also, bariatric surgery decreases oxidative stress parameters and glycoproteins and increases antioxidant enzymes paraoxonase-1 and catalase as well, which supports the idea that this procedure decreases oxidation of lipoproteins thus having antiatherogenic effects [34,35].…”
Section: Discussionmentioning
confidence: 76%
“…However, there was significant association between the changes in ox-LDL after bariatric surgery and percentage of BMI change. Some authors have tried to explain the beneficial effect of bariatric surgery on ASCVD by decreasing not only body weight, oxysterols, and ox-LDL but also by decreasing plasminogen activator inhibitor-1 (PAI-1), which is elevated in extremely obese patients and by decreased proliferation of vasa vasorum [35]. Bariatric surgery is a well-documented technique for weight loss can have numerous favorable con-sequences, such as rise in GLP-1 and its potential function in the metabolism including remission of T2DM [36].…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks of caloric restriction was shown to be associated with a decrease in blood myeloperoxidase activity and an increase in SOD activity [ 32 ]. It has also been documented that in patients with morbid obesity, OS is reduced after bariatric surgery [ 33 , 34 ]. On the other hand, a study involving obese young women treated for infertility lifestyle modification did not cause any significant change in OS assessed by fasting serum-free thiols concentration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational cohort first demonstrated that bariatric surgery decreases OS in patients with morbid obesity [ 34 ]. In that study, 24 patients with a BMI ≥ 40 kg/m 2 (mean BMI: 44.0 ± 7.03 kg/m 2 ) before BS were included.…”
Section: Discussionmentioning
confidence: 99%